2011
DOI: 10.1117/12.879053
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and performance of 3D mask models in optical projection lithography

Abstract: Different mask models have been compared: rigorous electromagnetic field (EMF) modeling, rigorous EMF modeling with decomposition techniques and the thin mask approach (Kirchhoff approach) to simulate optical diffraction from different mask patterns in projection systems for lithography. In addition, each rigorous model was tested for two different formulations for partially coherent imaging: The Hopkins assumption and rigorous simulation of mask diffraction orders for multiple illumination angles. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Continuous development of advanced computational lithography techniques are required to reduce the deterioration of image fidelity and increase the process window (PW) in ultra lowk 1 optical lithography [1]. One of the limitations to PW is the noticeable difference in best focus among various feature sizes [2,3]. This best focus shift effect, together with several other significant physical effects, is investigated in rigorous 3D mask simulations [4].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous development of advanced computational lithography techniques are required to reduce the deterioration of image fidelity and increase the process window (PW) in ultra lowk 1 optical lithography [1]. One of the limitations to PW is the noticeable difference in best focus among various feature sizes [2,3]. This best focus shift effect, together with several other significant physical effects, is investigated in rigorous 3D mask simulations [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Rigorous 3D mask experiments have confirmed that mask topography is a leading cause due to the fact that the thickness of the mask absorber produces phase errors among different diffraction orders. 2,3 Unfortunately, the rigorous electromagnetic field (EMF) modeling used to describe light diffraction from the mask generally involves intensive computation, 4 which limits the wide adoption of rigorous 3D mask modeling for practical large layout simulations in advanced resolution enhancement techniques (RETs) such as source and mask optimization (SMO). 5,6 Additionally, although SMO is a powerful and effective technique which provides more flexibility regarding both the mask design and illumination configuration adjustment, [7][8][9][10] it is inadequate to control the phase in the lens pupil.…”
Section: Introductionmentioning
confidence: 99%